Need for Reclassification of Forest Types in India Using High-resolution Satellite Data and Field Study for Better Management - Ramachandran, A.; Jayakumar, S.; Arockiasamy, D. I. (Indian Forester, 2005)
Forests, one of the important natural resources on the earth surface fulfill all the needs of living beings on the earth. For effective management of forests, it is important to have information on recent status, composition and types. Champion and Seth system of classification of Indian forest types has been used as an authentic source of information since it has been released for all management purposes. However one should remember that Champion and Seth classified the entire forests in India with limited technology, time and resources available with them. Hence there are certain forest areas where forest types are represented sporadically in the Champion and Seth system of classification. This classification naturally will have several shortcomings since it is done on macro scale. Now we have newer technologies, facilities like Remote Sensing, GIS, GPS with which we can understand the forests at micro-level and consequently more fine classification system could be evolved to reclassify the Forests in India. Eastern Ghats of Tamil Nadu is one such forest region, which has been taken up in the present study for further refinement. Remote sensing technique has been utilized appropriately in the present study for classification of forests with detailed field survey. Area belong to each forest type have been calculated accurately. The results of this study emphasize that refinement of forest types in India is necessary for better management of forests.